Duration of Soaking and Different Concentration of Order Against Crude Fiber Levels, Total Sugar and Organoleptic Quality of Okra Pudding (Abelmoschus esculentus) - Fatimah, Siti (Food Science and Technology Journal (Foodscitech), 2019)
Okra pudding is one of the dessert foods prepared from agar ingredients. Making okra as a pudding is expected to have more vitamin content than pudding in general. This study aims to determine the effect of different soaking time and agar concentration on crude fiber content, total sugar and organoleptic quality of okra pudding (Abelmoschus esculentus). This study used a Completely Randomized Design (CRD) with two factors, namely immersion time of okra (2, 3 and 4 hours) and agar concentration (2, 3 and 4%) each treatment was repeated 3 times. Determination of the best treatment of all research parameters was carried out using the effectiveness test. The results of the study showed that different lengths of fertilization and concentration had a significant effect on crude fiber content, total sugar and organoleptic quality.